2018
DOI: 10.3389/fnhum.2018.00129
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing of Joyful and Disgusting Food Pictures by Women With an Eating Disorder

Abstract: The present study used the presentation of food pictures and judgements about their duration to assess the emotions elicited by food in women suffering from an eating disorder (ED). Twenty-three women diagnosed with an ED, namely anorexia (AN) or bulimia nervosa (BN), and 23 healthy controls (HC) completed a temporal bisection task and a duration discrimination task. Intervals were marked with emotionally pre-rated pictures of joyful and disgusting food, and pictures of neutral objects. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 174 publications
(230 reference statements)
2
20
0
Order By: Relevance
“…Conversely, Experiment 2 showed that when exposed to a stimulating odor (lemon), participants overestimated durations. These findings are consistent with the numerous studies that report the distortion of time perception in other sensory modalities caused by arousal-based mechanisms (Droit-Volet et al, 2011;Droit-Volet, Ramos, et al, 2013;Frederickx et al, 2013;Gagnon et al, 2018;Noulhiane et al, 2007;Rattat et al, 2018) rather than attentional-based ones (for a review, see Lake et al, 2016 and for an opinion article, see . Within the theoretical frame of the internal clock that contains a pacemaker-accumulator device, we can conclude that the strawberry odor decelerated the pacemaker's rate of pulse emission, whereas the lemon odor accelerated it.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Conversely, Experiment 2 showed that when exposed to a stimulating odor (lemon), participants overestimated durations. These findings are consistent with the numerous studies that report the distortion of time perception in other sensory modalities caused by arousal-based mechanisms (Droit-Volet et al, 2011;Droit-Volet, Ramos, et al, 2013;Frederickx et al, 2013;Gagnon et al, 2018;Noulhiane et al, 2007;Rattat et al, 2018) rather than attentional-based ones (for a review, see Lake et al, 2016 and for an opinion article, see . Within the theoretical frame of the internal clock that contains a pacemaker-accumulator device, we can conclude that the strawberry odor decelerated the pacemaker's rate of pulse emission, whereas the lemon odor accelerated it.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, odors that are considered relaxing or stimulating were presented during a temporal bisection task. The temporal bisection task is commonly employed within the field of time perception (Grondin, 2010;Kopec & Brody, 2010) and emotions (e.g., Droit-Volet, Ramos, et al, 2013;Gagnon et al, 2018;Lake et al, 2016). It will allow us to distinguish whether the effects of odors are due to a state of arousal rather than a modification of attention.…”
Section: Time Distortions and The Relaxing And Stimulating Effects Of Odorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The backwards verbal digit span was the most recurring measure utilising the phonological loop. Of the studies directly comparing AN and HC cohorts in the verbal digit span, 57% of the studies did not detect any significant difference between the groups [55][56][57][58], while 43% found impairments in the AN participants [43,59,60] (Fig. 2B).…”
Section: Verbal and Auditory Domainsmentioning
confidence: 99%